Destination Irrational Procrastination: An Exploration of the Role of Attributional Thinking and Self-Regulation on Procrastination in Synchronous Online Graduate Students - Dunn, Karee; Hayakawa, Takuya (Online Learning, 2021)
The purpose of this study was to determine if internally directed attributions and perceived degree of engagement in self-regulation predicted the degree to which synchronous online graduate students procrastinate. Internally directed attributions to ability and effort and adaptive self-regulation of learning were selected as research suggests these variables are responsive to training (Greene & Azevedo, 2007; Hood, 2013). As a relationship among these variables had not yet been established in this population, the current results add to our burgeoning understanding of how to best support the success of our synchronous online graduate students.